2020
DOI: 10.3390/ma13204498
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Microstructure of Laser Powder Bed Fusion Produced Face-Centered-Cubic-Structured Equiatomic CrFeNiMn Multicomponent Alloy

Abstract: A cobalt-free equiatomic CrFeNiMn multicomponent alloy was fabricated from gas-atomized powder using laser powder bed fusion (L-PBF), also known as selective laser melting (SLM). The as-built specimens had a single face-centered cubic (FCC) structure, relative density of 98%, and hardness up to 248 HV0.5 for both the scanning speeds applied. In this work, we report the hierarchical microstructural features observed in the as-built specimens. These are comprised of melt pools, grains, cell structures including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…They concluded that the hydrogen would diffuse initially along the cell walls then into the interior of cells, and the abundant cell walls in the SLM 316L SS act as rapid transportation paths for the H atoms; therefore, it suggests that the higher average hydrogen concentrations in SLM specimens are attributed to the high contents of chromium and manganese, and the cellular structure in conjunction with the elemental segregation and the high density of dislocations in the cell walls. Particularly, the larger average hydrogen concentration in SLM-2 compared to that in SLM-1 is ascribed to the broader cell walls associated with more severe segregation into the cell walls, as revealed in our previous study [10].…”
Section: Hydrogen Uptake Abilitysupporting
confidence: 65%
See 4 more Smart Citations
“…They concluded that the hydrogen would diffuse initially along the cell walls then into the interior of cells, and the abundant cell walls in the SLM 316L SS act as rapid transportation paths for the H atoms; therefore, it suggests that the higher average hydrogen concentrations in SLM specimens are attributed to the high contents of chromium and manganese, and the cellular structure in conjunction with the elemental segregation and the high density of dislocations in the cell walls. Particularly, the larger average hydrogen concentration in SLM-2 compared to that in SLM-1 is ascribed to the broader cell walls associated with more severe segregation into the cell walls, as revealed in our previous study [10].…”
Section: Hydrogen Uptake Abilitysupporting
confidence: 65%
“…A summary of the composition and microstructure of the samples is given in Table 1. The detailed microstructure of the SLM-built samples has been described in [10]. It comprises fine dislocation cells with some segregation of Mn and Ni alloying elements into the cell walls, and boundaries of grains and melt pools.…”
Section: Defect Structurementioning
confidence: 99%
See 3 more Smart Citations